PENGARUH PENGETAHUAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR RODA DUA PADA PEGAWAI PLN UPDK BARITO BANJARMASIN (Studi kasus pada PLN UPDK Barito Banjarmasin) - Natasya Humaira Putri; Rara Gustiana (Sekolah Tinggi Ilmu Ekonomi Nasional (STIENAS) Banjarmasin, 2024)
The aim of the study was to empirically prove the effect of tax knowledge and tax and tax sanctions on taxpayer compliance in paying two-wheeled motor vehicle taxes in employees of the Banjarmasin PLN UPDK Barito. The method used in this study was a quantitative method by distributing questionnaires to 40 employees of the Banjarmasin PLN UPDK Barito who were used as respondents using the SPSS Version 26.00 test tool. The conclusion is that tax knowledge has a partial effect on taxpayer compliance, tax sanctions have no partial effect on taxpayer compliance, and tax knowledge and tax sanctions have a simultaneous effect on taxpayer compliance for employees of the Banjarmasin PLN UPDK Barito.